Adhesive material with triggerable on-demand detachment

CN115697426BActive Publication Date: 2026-10-20MASSACHUSETTS INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180040625.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-04
Filing Date
2021-05-24
Publication Date
2026-10-20
Estimated Expiration
2041-05-24

Smart Images

  • Figure HDA0003981331900000011
    Figure HDA0003981331900000011
  • Figure HDA0003981331900000021
    Figure HDA0003981331900000021
  • Figure HDA0003981331900000022
    Figure HDA0003981331900000022
Patent Text Reader

Abstract

An adhesive material that provides rapid and strong adhesion on wet surfaces, where the adhesion formed is releasable on demand. The adhesive material is formed from one or more hydrophilic polymers or copolymers grafted with one or more amine coupling groups through a plurality of cleavable physical and / or cleavable covalent bonds and one or more crosslinking agents. Application of the adhesive material on a wet surface causes the adhesive material to absorb liquid, thereby swelling the adhesive material to form a layer of hydrogel, allowing temporary crosslinking with the surface, and then covalent crosslinking with the surface. Introduction of a trigger agent cleaves the cleavable physical and / or cleavable covalent bonds to allow the adhesive material to be released non-invasively from the surface.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 63 / 034644, entitled “Antibody Liquid Tissue Adhesive,” filed June 4, 2020, the entire contents of which are incorporated herein by reference.

[0003] Government Support Statement This invention was made with government support, granted by the National Science Foundation under grant number EFMA-1935291. The government holds certain rights to this invention. Technical Field

[0004] This invention generally relates to adhesive materials and methods for adhering to surfaces, and more specifically, to dry biological adhesive materials and methods for adhering to wet tissue surfaces, wherein the adhesion formed between the adhesive material and the surface is removable on demand. Background Technology

[0005] Every year, millions of major surgeries are performed worldwide. While sutures and staples are most commonly used in these surgeries to close wounds, achieve hemostasis, and attach implantable devices to tissues, bioadhesives (such as tissue adhesives, hemostatic agents, and tissue sealants) are considered alternatives due to their potential advantages, such as ease of use, airtight or watertight seals, and the potential to reduce tissue damage. However, existing bioadhesives have shown some limitations.

[0006] It is generally understood that two dry surfaces can momentarily adhere to each other when they come into contact, through intermolecular forces such as hydrogen bonds, electrostatics, and van der Waals interactions. However, forming such momentary adhesion between wet surfaces (such as biological tissues) is very challenging because water separates the molecules from the two surfaces, creating momentary interactions that hinder adhesion between the surfaces.

[0007] Furthermore, existing tissue adhesives, primarily in the form of liquids or wet hydrogels, face numerous limitations, including weak binding, low biocompatibility, and poor mechanical compatibility with tissues. In particular, such as... Figure 1 As shown in A-1B, such existing tissue adhesives rely on their molecules (e.g., small / large monomers or polymers) to diffuse into the polymer network of the tissue to bind, which takes a long time and provides weak adhesion, and the presence of interfacial fluid between the adhesive and the tissue further interferes with the bonding process.

[0008] For example, commercially available adhesives (e.g., fibroin glue, albumin-based adhesives, polyethylene glycol-based adhesives), nanoparticle solutions, and mussel-inspired adhesives exhibit slow bond formation (over 1 minute) and weak adhesion on wet surfaces (interfacial toughness less than 20 J / m). -2 (See Vakalopoulos, KA) et al. Mechanical strength and rheological properties of tissue adhesives with regard to colorectalanastomosis: an ex vivo study. Annals of Surgery 261, 323-331 (2015); Rose, S. et al. Nanoparticle solutions as adhesives for gels and biological tissues. Nature 505, 382-385 (2014); Lee, BP, Messersmith, PB, Israelachvili, JN&Waite, JH Mussel-inspired adhesives andcoatings. Annual Review of Materials Research 41, 99-132 (2011)). Cyanoacrylate adhesives have been found to exhibit further high cytotoxicity and lack of flexibility after curing (see Annabi, N., Yue, K., Tamayol, A. & Khademhosseini, A. Elastic sealants for surgical applications). European Journal of Pharmaceutics and Biopharmaceutics 95, 27-39(2015); Karp, JM A Slick and Stretchable Surgical Adhesive. New England Journal of Medicine 377, 2092-2094 (2017)). The adhesion of bulk hydrogels to tissues with 100 to 1000 J / m² has been reported. -2 It exhibits interfacial toughness on the order of magnitude, but this hydrogel requires prolonged pressure application of at least 10 to 30 minutes to form adhesion (see Li, J). et al. Tough adhesives for diverse wetsurfaces. Science 357, 378-381 (2017)).

[0009] Furthermore, in medical procedures, repositioning misplaced adhesives or retrieving implanted devices secured with adhesives is crucial. However, few reversible adhesives have been developed, and those that are available have significant drawbacks. Most adhesives typically rely on harsh, non-biocompatible triggering conditions (such as concentrated metal ions, heat, or ultraviolet (UV) radiation) for their detachment, which is detrimental to the adhesive, the tissue to which it is attached, and adjacent natural tissue.

[0010] Given the enormous potential of tissue adhesives, especially in medical applications, improvements are urgently needed. Summary of the Invention

[0011] According to one aspect, the present invention provides an adhesive material for bonding one or more wet surfaces and for triggerable detachment from one or more surfaces, the adhesive material comprising: (i) one or more hydrophilic polymers or copolymers grafted with (ii) one or more amine coupling groups via (iii) a plurality of cleavable physical bonds and / or cleavable covalent bonds, and (iv) one or more crosslinking agents, wherein the adhesive material is in the form of a film or tape having a top surface and a bottom surface, and wherein the adhesive material has liquid contents such that placement of one or more of the top surface and / or bottom surface of the adhesive material in contact with one or more wet surfaces causes the adhesive material to absorb liquid from one or more wet surfaces, swell to form a temporary crosslink between the dry adhesive material and the wet surface, and form covalent bonds between one or more amine coupling groups and one or more wet surfaces.

[0012] Embodiments of this aspect may include one or more of the following features: (i) one or more hydrophilic polymers or copolymers selected from polyacrylic acid, polyacrylamide, polyvinyl alcohol, polyhydroxyethyl methacrylate, polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginate, oxidized alginate, cellulose, oxidized cellulose, polyvinylpyrrolidone, polystyrene sulfonate, collagen, pectin, and combinations thereof. (ii) one or more amine coupling groups selected from... N 2-hydroxysuccinimide ester, N- Hydroxysulfosuccinimide esters, aldehydes, imine esters, epoxides, isocyanates, catechols, and combinations thereof. (iii) The cleavable physical bonds are selected from hydrogen bonds, electrostatic bonds, and host-guest bonds, and the cleavable covalent bonds are selected from boron-oxygen bonds, phenylboronic esters, disulfide bonds, hydrazone bonds, imine bonds, Diels-Alder bonds, carbon-carbon / carbon-sulfur bonds, and oxime bonds. The host-guest bond is selected from α-cyclodextrin (CD) as the host and n-butyl (n-Bu) group, adamantyl group, benzyl group, and trans-azophenyl group as the guest; βCD as the host and adamantyl group, tert-butyl group, cyclohexyl (ester) group, cyclododecyl (amide) group, benzyl group, 2-naphthylmethyl group, 1-pyrene methyl group, ferrocene group, and trans-azophenyl group as the guest; and γCD as the host and cyclododecyl group, benzyl group, 2-naphthylmethyl group, 9-phenanthylmethyl group, and 1-pyrene methyl group as the guest. (iv) One or more crosslinking agents are selected from gelatin methacrylate, hyaluronic acid methacrylate, oxidized methacrylate alginate, polycaprolactone diacrylate, N,N' -Bis(acryloyl)cystamine, N,N' - Methylene bis(acrylamide), polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and combinations thereof. The adhesive material comprises, in a dry state, an interpenetrating network of (i) polyvinyl alcohol (PVA) and poly(acrylic acid) (PAA), the poly(acrylic acid) being grafted with (ii) cleavable disulfide bonds via (iii) cleavable disulfide bonds. N- Hydroxysuccinimide (NHS) ester. Grafted with N - The negatively charged carboxylic acid groups in the poly(acrylic acid) of hydroxysuccinimide ester promote liquid absorption and swelling of the dry adhesive material, and further form intermolecular bonds with one or more wet tissue surfaces within less than 60 seconds after the dry adhesive material comes into contact with one or more wet tissue surfaces. The N-hydroxysuccinimide ester grafted onto the poly(acrylic acid) forms cleavable covalent bonds with primary amine groups present on one or more wet surfaces. After covalent crosslinking between one or more amine coupling groups and one or more wet surfaces, the swollen adhesive material transforms into a hydrogel. The hydrogel has a viscosity of at least about 1000 J / m³. -2 The adhesive material exhibits high fracture toughness. It is in the form of a flat sheet, perforated sheet, double-sided tape, or film, or a perforated double-sided tape or film. The adhesive material includes a top surface and a bottom surface, and further comprises one or more backing material layers disposed on at least one of the top and bottom surfaces. The adhesive material also includes one or more engineered solids and / or devices adhered to one or more surfaces of the adhesive material. The adhesive material is biodegradable.

[0013] According to another aspect, the present invention provides a method for bonding wet tissue with an adhesive material and removing the adhesive material as needed, the method comprising: providing an adhesive material, wherein the adhesive material comprises (i) one or more hydrophilic polymers or copolymers grafted with (ii) one or more amine coupling groups via (iii) a plurality of cleavable physical bonds and / or cleavable covalent bonds, and (iv) one or more crosslinking agents; placing the adhesive material in contact with one or more wet surfaces of the wet tissue; allowing the adhesive material to absorb liquid from the one or more wet surfaces, thereby causing the adhesive material to swell to form a hydrogel; allowing temporary crosslinking to form between the adhesive material and the surface; optionally allowing covalent bonds to form between the one or more amine coupling groups and the one or more wet surfaces; introducing a triggering agent under physiological conditions to cleave the cleavable physical bonds and / or cleavable covalent bonds; and detaching the adhesive material from the one or more surfaces.

[0014] Embodiments of this aspect may include one or more of the following features: (i) one or more hydrophilic polymers or copolymers selected from polyacrylic acid, polyacrylamide, polyvinyl alcohol, poly(hydroxyethyl methacrylate), polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginate, oxidized alginate, cellulose, oxidized cellulose, polyvinylpyrrolidone, polystyrene sulfonate, collagen, pectin, and combinations thereof. (ii) one or more amine coupling groups selected from... N 2-hydroxysuccinimide ester, N - Hydroxysulfosuccinimide esters, aldehydes, imine esters, epoxides, isocyanates, catechols, and combinations thereof. (iii) The cleavable physical bonds are selected from hydrogen bonds, electrostatic bonds, and host-guest bonds, and the cleavable covalent bonds are selected from boron-oxygen bonds, phenylboronic esters, disulfide bonds, hydrazone bonds, imine bonds, Diels-Alder bonds, carbon-carbon / carbon-sulfur bonds, and oxime bonds. The host-guest bond is selected from α-cyclodextrin (CD) as the host and n-butyl (n-Bu) group, adamantyl group, benzyl group, and trans-azophenyl group as the guest; βCD as the host and adamantyl group, tert-butyl group, cyclohexyl (ester) group, cyclododecyl (amide) group, benzyl group, 2-naphthylmethyl group, 1-pyrene methyl group, ferrocene group, and trans-azophenyl group as the guest; and γCD as the host and cyclododecyl group, benzyl group, 2-naphthylmethyl group, 9-phenanthylmethyl group, and 1-pyrene methyl group as the guest. (iv) One or more crosslinking agents are selected from gelatin methacrylate, hyaluronic acid methacrylate, oxidized methacrylate alginate, polycaprolactone diacrylate, N,N' -Bis(acryloyl)cystamine, N,N'- Methylene bis(acrylamide), polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and combinations thereof. The adhesive material comprises, in a dry state, an interpenetrating network of (i) polyvinyl alcohol (PVA) and poly(acrylic acid) (PAA), the poly(acrylic acid) being grafted with (ii) cleavable disulfide bonds via (iii) cleavable disulfide bonds. N -Hydroxysuccinimide (NHS) ester. Under a pressure of no more than about 1 kPa applied for no more than 5 seconds, the PVA and PAA networks absorb liquid, causing one or more wet surfaces to dry. The PAA network provides carboxylic acid groups that form transient physical crosslinks with one or more surfaces via hydrogen bonds, and optionally, cleavable NHS ester groups grafted onto the PAA network form stable covalent crosslinks with primary amine groups on one or more surfaces. A pH-dependent decrosslinking trigger is used to cleave the physical bonds. The pH-dependent decrosslinking trigger is sodium bicarbonate. A biocompatible reducing agent is used to cleave the covalent bonds. The biocompatible reducing agent is glutathione. The trigger comprises a solution containing a combination of sodium bicarbonate and glutathione.

[0015] Other systems, methods, and features of the present invention will be apparent or become apparent to those skilled in the art upon viewing the following figures and detailed description. It is intended that all such additional systems, methods, and features are included in this specification, within the scope of the invention, and protected by the appended claims. Attached Figure Description

[0016] The accompanying drawings are included to provide a further understanding of the invention, and are incorporated in and constitute a part of this specification. The components in the drawings are not necessarily to scale, but are emphasized to clearly illustrate the principles of the invention. The drawings illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0017] Figure 1 A-1C schematically illustrates a tissue adhesive according to the prior art, wherein, Figure 1 A describes existing tissue adhesives in liquid form. Figure 1 B describes existing tissue adhesives in the form of wet hydrogels, and Figure 1 C illustrates a schematic diagram of the mechanism of existing tissue adhesives, which relies on monomers or polymers diffusing into the polymer network of the tissue for binding.

[0018] Figure 2A-2C An example of a cleavable host-guest physical bond according to an embodiment of the present invention is illustrated, wherein, Figure 2A The diagram illustrates the guest of the αCD host and the corresponding bond-breaking trigger. Figure 2B The diagram illustrates the guest of the βCD host and the corresponding bond-breaking triggers, as well as... Figure 2CThe diagram illustrates the guest of the γCD host and the corresponding bond-breaking trigger.

[0019] Figure 3 Examples of cleavable covalent bonds and corresponding bond cleavage triggers according to embodiments of the present invention are illustrated.

[0020] Figures 4A-4C The design and mechanism of a transient, robust, and triggerable detachable bioadhesive according to an embodiment of the present invention are schematically illustrated, wherein, Figure 4A The design of the bio-adhesive, dry crosslinking, and triggerable separation mechanism is illustrated schematically. Figure 4B The diagram schematically illustrates the decrosslinking process of decomposable physical crosslinks via sodium bicarbonate, and... Figure 4C The diagram schematically illustrates the decrosslinking process of cleavable covalent crosslinks via glutathione.

[0021] Figure 5 The illustrations schematically depict the bonding and triggerable detachment requirements of the bio-adhesive material at different time ranges according to embodiments of the present invention.

[0022] Figure 6 A-6C illustrates a chemical scheme for the synthesis of a functional monomer according to an embodiment of the present invention.

[0023] Figure 7 The diagram graphically depicts the NHS ester-functionalized monomer with disulfide bonds synthesized according to embodiments of the present invention. 1 H NMR spectrum.

[0024] Figure 8 Figure A-8J illustrates a triggerable detachment of a bio-adhesive material according to an embodiment of the present invention, wherein... Figure 8 A graphical depiction of a substance containing carboxylic acid (1698 cm) -1 ), disulfide (614cm) -1 ) and NHS esters (1162 and 1232 cm -1 FTIR spectra of bioadhesive materials with functional group-related peaks. Figure 8 B schematically illustrates the verification of triggerable detachment based on fluorescent primary amine-coupled microbeads. Figure 8 C-8F shows the initial state ( Figure 8 C) In PBS ( Figure 8 D) PBS with 0.5 SBC ( Figure 8 E) and PBS with 0.5M SBC and 50mM GSH ( Figure 8 Fluorescence microscopy image of the bioadhesive sample 5 minutes after incubation in F). Figure 8 G shows a photograph of the 180-degree peel test setup used to measure interfacial toughness, and Figure 8The H-8J illustration shows its capabilities in the short term ( Figure 8 H), Mid-term ( Figure 8 I) and long-term ( Figure 8 J) The interfacial toughness between the bio-adhesive and wet porcine skin tissue 5 minutes after the application of various solutions during the bonding process. Figure 8 The values ​​in H-8J represent the mean and standard deviation (n=4). These are determined by a Student's t-test. P Value; ns, not significant ( p >0.05); p ≤ 0.05; p ≤ 0.01; p ≤ 0.001. A scale bar is shown in the image.

[0025] Figure 9 Graphically depicted in Figure 3 The number of fluorescent microbeads adhering to the bioadhesive according to an embodiment of the present invention after 5 minutes of incubation in different solutions depicted in C-3F. Values ​​represent the mean and standard deviation (n=4). Determined by Student's t-test. P Value; ns, not significant ( p >0.05); p ≤0.05; p ≤0.01.

[0026] Figure 10 The diagram schematically illustrates a mechanical test setup for measuring interfacial toughness based on the standard 180-degree peel test (ASTM F2256).

[0027] Figure 11 A-11B schematically illustrates the effect of pH on the adhesive properties of a bio-adhesive according to an embodiment of the present invention, wherein... Figure 11 A shows the various pH values ​​in the human body, and Figure 11 Figure B illustrates the interfacial toughness between a bioadhesive and wet porcine skin tissue incubated in PBS at various pH adjustments. Figure 11 The values ​​in B represent the mean and standard deviation (n=3). These were determined using one-way ANOVA and Tukey's multiple comparisons experiment. P Value; ns, not significant ( p >0.05).

[0028] Figure 12A-12B graphically depicts the triggerable detachment efficiency of a bio-adhesive according to an embodiment of the present invention, wherein... Figure 12 Figure A illustrates the interfacial toughness between the bioadhesive and wet porcine skin tissue in the absence of triggering, and at 1, 5, 10, and 30 minutes after application of the triggering solution. Figure 12 Figure B shows a representative force / width-to-displacement curve for a 180-degree peel test. Figure 12 The values ​​in A represent the mean and standard deviation (n=4). These are determined by a Student's t-test. P Value; ns, not significant ( p >0.05); p ≤0.05.

[0029] Figure 13 A-13C is graphically illustrated. Figure 3 H-3J medium and short term ( Figure 13 A) Mid-term ( Figure 13 B) and long-term ( Figure 13 C) Representative force / width relative displacement curves from the 180-degree peel test of the adhesive.

[0030] Figure 14 A-14E illustrates the in vivo applicability and biocompatibility of a bioadhesive according to an embodiment of the present invention, wherein... Figure 14 Figure A shows a photograph illustrating the instantaneous strong adhesion and triggerable detachment of a bioadhesive in the subcutaneous space of rats in vivo. Figure 14 B-14D illustrates a representative histological image stained with H&E, used in sham surgery. Figure 14 B) Triggered disassembly of bioadhesives ( Figure 14 C) and implanted bioadhesive ( Figure 14 Biocompatibility assessment of D), and Figure 14 Figure E illustrates the degree of inflammation (0, normal; 1, very mild; 2, mild; 3, moderate; 4, severe; 5, very severe) assessed by a blinded pathologist two weeks after subcutaneous implantation in the sham surgery group, the bioadhesive-triggered removal group, and the implanted bioadhesive group. SM and GT represent skeletal muscle and granulation tissue, respectively. All experiments were repeated four times, with similar results. Figure 14 The values ​​in E represent the mean and standard deviation (n=4). The p-value was determined by a Student's t-test; ns, not significant (p>0.05). A scale bar is shown in the graph.

[0031] Figure 15 A-15F illustrates a potential application of a bio-adhesive material according to an embodiment of the present invention, wherein... Figure 15 A-15B schematically illustrates ( Figure 15 A) and illustrated in the photograph ( Figure 15B) Correction of misplaced bioadhesives and instantaneous sealing of torn detached pig lungs using bioadhesive materials. Figure 15 The C-15D is schematically illustrated as follows ( Figure 15 C) and the photographic illustration shows ( Figure 15 D) Patterned bioadhesive materials for easy delivery and diffusion of trigger solutions in impermeable devices, and Figure 15 The E-15F is schematically illustrated as follows ( Figure 15 E) and illustrated in the photograph ( Figure 15 F) Instantly and firmly bonded to and removed on demand by bioadhesive materials on a beating, isolated pig heart.

[0032] Figure 16 A-16B schematically and graphically illustrates the effect of triggerable re-application and re-application of a bio-adhesive according to an embodiment of the present invention on adhesive properties, wherein... Figure 16 A schematic illustration shows a bio-adhesive material that can be triggered for removal and reapplication, and Figure 16 B illustrates the interfacial toughness between wet pig skin and the initially applied bioadhesive material, as well as the bioadhesive material reapplied to the same tissue after triggerable detachment. Figure 16 The values ​​in B) represent the mean and standard deviation (n=3). These are determined by a Student's t-test. P Value; ns, not significant ( p >0.05). Detailed Implementation

[0033] The following definitions are useful for explaining the terms that apply to the features of the embodiments disclosed herein, and are used only to define elements in this disclosure.

[0034] As used herein, when describing the adhesive materials of the present invention, the term "dry" refers to a material with a moisture content below its equilibrium moisture content during use. Therefore, when the dry adhesive material of the present invention is placed in contact with wet tissue or other wet or moistened (e.g., saline-wetted) surfaces to which it will adhere, the material will absorb fluids (e.g., water, saline, moisture, and physiological fluids such as plasma, interstitial fluid, lymph, cerebrospinal fluid, and gastrointestinal fluid) from the wet or moistened surfaces. Typically, based on the total weight of the dry adhesive material, the dry adhesive material has less than about 50% by weight of liquid component.

[0035] As used herein, when describing the mechanism by which dry adhesive materials absorb water, saline, moisture, and physiological fluids (such as plasma, interstitial fluid, lymph, cerebrospinal fluid, and gastrointestinal fluid) from wet surfaces in contact with them, the term "absorption" refers to the passage of atoms or molecules of liquids from wet surfaces through the surface of the dry adhesive material and into the dry adhesive material.

[0036] As used herein, when describing the adhesive materials of the present invention, the terms "ribbon" or "film" refer to a structure having a relatively large area relative to its thickness. This structure provides flexibility.

[0037] As used herein, when describing the adhesive materials of the present invention, the term "double-sided" refers to an adhesive tape or film that provides adhesive properties on both the top and bottom surfaces of the adhesive. It should be noted that while an adhesive material may be referred to as double-sided, the adhesive properties of the adhesive material may be single-sided or double-sided for a given application. For example, during use, it may be desirable to utilize only the adhesive properties of one side of the adhesive material, and not to utilize the adhesive properties of the second side (e.g., by maintaining a material layer or backing material on the second side surface during use to block the adhesive properties on that second side). In such instances, a material layer or backing material may initially be provided on both the first and second sides, and the material layer or backing material may be removed only from the first side prior to application, so that only the adhesive properties of the first side can be used.

[0038] As used herein, the term “wet tissue” refers to biological tissue that contains or is covered (partially or completely covered) with fluids, including water, saline, moisture, and physiological fluids such as plasma, interstitial fluid, lymph, cerebrospinal fluid, and gastrointestinal fluid.

[0039] As used herein, when describing a transient temporary crosslinking between an adhesive material and one or more wet surfaces, the term "transient" means the time elapsed from the instant the adhesive material comes into contact with the one or more wet surfaces that is greater than zero seconds, at most one minute or less than one minute, more preferably less than or equal to about 50 seconds, more preferably less than or equal to about 40 seconds, more preferably less than or equal to about 30 seconds, more preferably less than or equal to about 20 seconds, more preferably less than or greater than about 15 seconds, more preferably less than or equal to about 10 seconds, more preferably less than or equal to about 9 seconds, more preferably less than or equal to about 8 seconds, more preferably less than or equal to about 7 seconds, more preferably less than or equal to about 6 seconds, and more preferably less than or equal to about 5 seconds.

[0040] As used herein, when used to describe transient temporary crosslinking between an adhesive material and one or more wet surfaces, the term "temporary" refers to a time range that extends between the time it takes for the transient temporary crosslinking to form and a sufficiently long time (e.g., more than 24 hours after the formation of the transient temporary crosslinking).

[0041] As used herein, when used to describe rapid covalent crosslinking between an adhesive material and one or more wet surfaces, "rapid" or "rapid" means that the time elapsed from the moment the adhesive material comes into contact with one or more wet surfaces is greater than zero seconds, up to and including 5 minutes, more preferably less than or equal to about 4.5 minutes, more preferably less than or equal to about 4 minutes, more preferably less than or equal to about 3.5 minutes, more preferably less than or equal to about 3 minutes, more preferably less than or equal to about 2.5 minutes, more preferably less than or equal to about 2 minutes, more preferably less than or equal to about 1.5 minutes, and more preferably less than or equal to about 1 minute.

[0042] As used herein, when describing the absorption and swelling of a dry adhesive material upon contact with one or more wet surfaces, "swelling" generally refers to an increase in the size of the dry adhesive material. Dry adhesive materials are typically in the form of tapes or films, which become thicker after absorbing liquid.

[0043] As used herein, when describing adhesive materials, "biodegradable" means partially or completely broken down in a living animal by endogenous enzymes and / or water and / or subsequently removed from the implant material.

[0044] As used in this article, “engineered solids” refers to solid materials that are not biological tissues, including synthetic materials such as plastics, metals, glass, ceramics and elastomers, as well as biomaterials processed from natural sources.

[0045] As used herein, when referring to the on-demand removal of adhesive material from one or more surfaces to which it is attached, "on-demand" means removal at any desired time after the adhesive material has been applied to the target surface, and is accomplished by applying or introducing a triggering mechanism to the adhesive material, the surface, and / or between the surface and the adhesive material. The triggering mechanism is used to break the crosslinks between the adhesive material and one or more surfaces. Specifically, after the application or introduction of the triggering mechanism, the adhesive material can be removed from the surface with little or no trauma within approximately 20 minutes, more preferably within approximately 10 minutes, and even more preferably within approximately 5 minutes by simply grasping the adhesive material (e.g., with tweezers) and pulling it away from the surface.

[0046] This invention generally provides an adhesive material capable of adhering to and bonding wet surfaces (particularly wet tissue surfaces) together. This adhesive material is a dry adhesive material prepared to provide a dry crosslinking mechanism for instantaneous strong bonding of wet surfaces. Specifically, the dry adhesive material is prepared such that when placed in contact with one or more wet surfaces, it absorbs liquid from the one or more wet surfaces, causing the adhesive material to swell. This absorption of the interfacial liquid allows for instantaneous crosslinking via intermolecular interactions between the adhesive material and the one or more wet surfaces, followed by rapid covalent crosslinking between the adhesive material and the one or more wet surfaces (see...). Figures 4A-4B ).like Figures 4A-4B As shown, the cleavable physical crosslinks and covalent crosslinks are disposed between the hydrophilic polymer / copolymer and the chemical groups that form crosslinks with one or more wet surfaces. In addition to forming immediate strong adhesion on various wet dynamic tissues, the adhesive material of the present invention can be detached from the adhered surface on demand by using a triggering material. Specifically, the adhesive material can be detached from the adhered surface at any desired time by a triggering mechanism, particularly a biocompatible trigger. For example, by contacting the adhesive material with a triggering mechanism, the triggering mechanism acts to cleave the cleavable physical crosslinks and covalent crosslinks (e.g., as...). Figures 4A-4B As shown in the figure, this allows the adhesive material to be removed from the surface.

[0047] The adhesive material of the present invention thus overcomes the above-mentioned limitations of existing adhesive materials (such as...). Figure 1 (Further described in A-1C). Instead of the tissue-diffusion molecules required by existing adhesive materials, the dry adhesive material of the present invention achieves instantaneous strong adhesion to wet surfaces by synergistically combining the drying of the interfacial liquid through swelling of the dry adhesive material, transient temporary crosslinking between the adhesive material and one or more wet surfaces, and rapid covalent crosslinking. By using the adhesive structure and triggering mechanism, the adhesive material of the present invention further provides on-demand detachment from the surface to which it is adhered, which reduces tissue trauma and eliminates the need for harsh non-biocompatible triggering conditions (e.g., concentrated metal ions, heat, and ultraviolet (UV) irradiation) for removal.

[0048] As further described below, in vitro and ex vivo models demonstrate that the adhesive material of the present invention can achieve strong adhesion between different wet dynamic tissues (e.g., skin, tendons, stomach, muscles, heart, and liver) and engineered solids within seconds (e.g., within 5 seconds), and exhibits high interfacial toughness (e.g., exceeding 400 J / m). -2 More than 500 J m -2 More than 600 J m -2 More than 700 J m -2 More than 800 J m -2More than 900 J m -2 Even exceeding 1000 J m -2 It also provides properties comparable to those found in biological tissues, including low shear modulus (e.g., about 20 kPa or less, about 15 kPa or less, and even about 10 kPa), shear and tensile strength on the order of about 160 kPa, and high tensile strength (e.g., on the order of 7, 8, 9, or even 10 times the original unstretched size), high biocompatibility, and controllable biodegradability. As further demonstrated, the adhesive material can be easily removed at any time after bonding by using a triggering mechanism.

[0049] Therefore, the dry adhesive material of the present invention not only provides a new paradigm of wet bonding, which enables new opportunities in a variety of applications such as tissue adhesives, biological scaffolds, drug delivery and wearable and implantable devices, but also further provides on-demand, non-invasive removal.

[0050] Reference will now be made in detail to embodiments of the invention, examples of which are illustrated in the accompanying drawings. Where possible, the same reference numerals are used in the figures and description to denote the same or similar parts.

[0051] According to one aspect, the present invention provides an adhesive material comprising a combination of: (i) one or more hydrophilic polymers or copolymers grafted with (ii) one or more amine coupling groups via (iii) cleavable physical bonds and / or cleavable covalent bonds, and (iv) one or more crosslinking agents.

[0052] Adhesive materials are typically in the form of dry materials because when placed in contact with one or more wet surfaces (e.g., wet tissue), they absorb liquid from these surfaces, thereby removing the interfacial liquid present between the adhesive material and the wet surface. This liquid absorption causes the dry material to swell. The absorption of liquid and the swelling of the dry adhesive material provide a transient, temporary crosslinking between the adhesive material and the wet surface, and further allow for subsequent rapid covalent coupling or crosslinking between the adhesive material and one or more wet surfaces, as further described herein.

[0053] According to embodiments of the invention, (i) one or more hydrophilic polymers or copolymers are selected from any conventional hydrophilic polymers that absorb water in a dry state, including but not limited to polyacrylic acid, polyacrylamide, polyvinyl alcohol, poly(hydroxyethyl methacrylate), polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginate, oxidized alginate, cellulose, oxidized cellulose, polyvinylpyrrolidone, polystyrene sulfonate, collagen, pectin, and combinations thereof. Since the adhesive materials of the present invention can be used in a variety of biomedical applications, the polymers and copolymers used in the present invention are preferably biocompatible (although for non-biomedical applications, it is not necessary to use only biocompatible polymer materials). According to a preferred embodiment, the one or more hydrophilic polymers contain one or more negatively charged groups, such as poly(acrylic acid), casein, albumin, and alginate, the negatively charged groups of which impart hygroscopic properties, which are desirable for the rapid absorption and removal of interfacial liquids on wet surfaces.

[0054] According to an embodiment of the present invention, (ii) one or more amine coupling groups are selected from conventional amine coupling groups, including but not limited to... N 2-hydroxysuccinimide ester, N - Hydroxysulfosuccinimide esters, aldehydes, imine esters, epoxides, isocyanates, catechols, and combinations thereof. Since the adhesive materials of the present invention can be used in a variety of biomedical applications, the amine coupling groups used in the present invention are preferably biocompatible (although for non-biomedical applications, it is not necessary to use only biocompatible amine coupling groups). Such amine coupling groups are configured such that one or more hydrophilic polymers can be grafted with one or more amine coupling groups via cleavable bonds, and such that the one or more amine coupling groups subsequently form a covalent crosslink with the wet surface on which the adhesive material is applied.

[0055] According to an embodiment of the present invention, (iii) the cleavable physical bond is selected from conventional bonds of this type, including but not limited to hydrogen bonds, electrostatic bonds, and host-guest bonds, wherein the host-guest bond includes α-cyclodextrin (CD) as the host and n-butyl (n-Bu) group, adamantyl group, benzyl group, and trans-azophenyl group as the guest; βCD as the host and adamantyl group, tert-butyl group, cyclohexyl (ester) group, cyclododecyl (amide) group, benzyl group, 2-naphthylmethyl group, 1-pyrene methyl group, ferrocene group, and trans-azophenyl group as the guest; γCD as the host and cyclododecyl group, benzyl group, 2-naphthylmethyl group, 9-phenanthylmethyl group, and 1-pyrene methyl group as the guest (for example, see Figure 2). Cleavable covalent bonds can also be selected from conventional such bonds, including but not limited to boron-oxygen bonds (including borate diol, phenyl borate ester), disulfide bonds, hydrazone bonds, imine bonds, Diels-Alder bonds, carbon-carbon / carbon-sulfur bonds (including trithiocarbonate (TTC) and thiuram disulfide (TDS)), and oxime bonds (e.g., see Figure 2).

[0056] According to an embodiment of the present invention, (iv) one or more crosslinking agents are selected from conventional crosslinking agents, including but not limited to gelatin methacrylate, hyaluronic acid methacrylate, oxidized alginate methacrylate, polycaprolactone diacrylate, etc. N,N' -Bis(acryloyl)cystamine, N,N' - Methylene bis(acrylamide), polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and combinations thereof. Since this adhesive material can be used in a variety of biomedical applications, the crosslinking agent used in this invention is preferably biocompatible (although for non-biomedical applications, it is not necessary to use only biocompatible crosslinking agents).

[0057] According to a preferred embodiment, the adhesive material comprises, in its freshly prepared (before drying) form: (i) about 5 w / w% to about 50 w / w% of one or more hydrophilic polymers, (ii) about 1 w / w% to about 10 w / w% of one or more amine coupling groups grafted by (iii) cleavable physical bonds and / or covalent bonds, and (iv) about 0.05 w / w% to about 0.15 w / w% of one or more crosslinking agents, and the remainder of deionized water.

[0058] According to a specific embodiment of the invention, the adhesive material is a bioadhesive material formed from an interpenetrating network of (i) polyvinyl alcohol (PVA) and poly(acrylic acid) (PAA) in a dry state, wherein the poly(acrylic acid) is grafted with (ii) N-hydroxysuccinimide (NHS) ester via (iii) cleavable disulfide bonds. The instantaneous adhesion of the adhesive material depends on the removal of interfacial water and / or other physiological fluids (such as saline, interstitial fluid, intracellular fluid, etc.) from wet surfaces (particularly wet tissue surfaces) through the highly hygroscopic PAA network in the bioadhesive (see, for example, see...). Figure 4A The PAA network simultaneously forms transient physical crosslinks with the surface (e.g., hydrogen bonds and electrostatic interactions). The subsequent covalent crosslinking of the cleavable NHS esters in the bioadhesive material with primary amine groups on the tissue surface further enhances long-term adhesive stability and strength. Figure 4A ).

[0059] According to a preferred embodiment, the adhesive material is a poly(vinyl alcohol) (PVA) based adhesive material. The PVA-based adhesive material according to an embodiment of the invention preferably comprises, in its freshly prepared (before drying) form: about 20 w / w% to about 40 w / w%, more preferably about 25 w / w% to about 35 w / w%, even more preferably about 30 w / w% of polyacrylic acid; about 5 w / w% to about 15 w / w%, more preferably about 10 w / w% of PVA; about 0.5 w / w% to about 1.5 w / w% of PAAc-disulfide-NHS ester, more preferably about 1 w / w% of PAAc-disulfide-NHS ester; about 0.01 w / w% to about 0.1 w / w% of poly(ethylene glycol methacrylate) (PEGDMA), more preferably about 0.05 w / w% of PEGDMA; and the remainder being deionized water.

[0060] According to an exemplary embodiment, the gelatin-based adhesive contains approximately 35 w / w% polyacrylic acid, approximately 10 w / w% PVA, approximately 1 w / w% PAAc-disulfide-NHS ester, approximately 0.05 w / w% PEGDMA, and the remainder of deionized water in its freshly prepared (before drying) form.

[0061] According to embodiments of the invention, the adhesive material has a top surface and a bottom surface. Preferably, the adhesive material is typically in the form of a sheet, tape, or film having a top surface and a bottom surface (all of which may be perforated, partially perforated, or non-perforated). In a preferred embodiment, the adhesive material has a removable backing layer or an integral (non-removable) material layer disposed on one or more adhesive surfaces. For example, one or more removable backing material layers may be disposed on one or more adhesive surfaces, particularly to aid in handling the adhesive material and provide moisture protection. If desired, one or more integral material layers may be disposed on one or more adhesive surfaces, particularly to provide one or more non-adhesive surfaces or partial surfaces for single-sided or partial-sided use.

[0062] For example, the entire top surface of an adhesive material may have a removable backing layer disposed thereon, while the entire bottom surface may have an integral material layer disposed thereon. Thus, by removing the backing layer before use, only the adhesive properties of the top surface of the adhesive material can be used in the application. Similarly, both the entire top and bottom surfaces may have removable backing layers disposed thereon, such that by removing the backing layer before use, the adhesive properties of both the top and bottom surfaces of the adhesive material can be used in the application. In some applications, it may be desirable to have a combination of one or more removable backing layers disposed on a single surface (e.g., the top surface) and an integral material layer also disposed on the same single surface (e.g., the top surface), such that by removing the backing layer from the portions of the surface (e.g., the top surface) on which the removable backing layer is disposed, only the adhesive properties of those portions can be used, without utilizing the adhesive properties of those portions of the surface (e.g., the top surface) on which the integral backing material layer is disposed. For example, the central portion of the top surface of the adhesive material may have an integral material layer disposed thereon, while the portions of the top surface surrounding the central portion may have one or more removable backing layers disposed thereon. This would provide a configuration in which, after the removable backing layer is removed, the top surface of the adhesive material adheres to the wet surface along the outer portion or periphery of the adhesive material, while the central portion of the adhesive material does not adhere due to the integral material layer that is not removed.

[0063] An integral material layer or a removable backing layer is provided to prevent the material from adhering before its intended use time. Therefore, the removable backing layer or integral material layer is a layer that blocks the adhesive properties of the material. An integral material layer or a removable backing layer is provided to prevent the material from adhering to non-target tissues during and after application to wet tissue. Therefore, the integral material layer or removable backing layer is a non-adhesive layer to wet biological tissue. The removable backing layer or integral material layer may be directly disposed on one or more surfaces of the adhesive material (i.e., nothing is disposed therebetween). In some embodiments, a layer or adhesive or other substance for bonding the materials together is disposed between one or more surfaces of the adhesive material and the integral material layer or removable backing layer. The removable backing layer or integral material layer may be made of any substance that prevents the adhesive material from adhering to wet surfaces. The integral material layer or removable backing layer may be made of any substance that does not adhere to wet biological tissue. In particular, as described herein, the adhesive material is in the form of a dry material that, when placed in contact with a wet surface, absorbs liquid from the wet surface, causing the dry material to swell. The absorption of this liquid and the swelling of the dry adhesive material provide instantaneous temporary crosslinking between the adhesive material and the wet surface, and further allow for subsequent rapid covalent coupling or crosslinking between the adhesive material and the wet surface. Thus, the removable backing layer or integral material layer can generally be made of any material that prevents contact between the liquid and the surface of the adhesive material. Thus, the integral material layer or backing layer can generally be made of any material that does not form an adhesive interface with wet biological tissue. Due to the use of the adhesive material of the present invention, the removable backing layer or integral material layer should be made of a biocompatible material. According to embodiments of the present invention, the removable backing layer is made of paper coated with polyethylene or any hydrophobic polymer and poly(methyl methacrylate) or any hydrophobic polymer film. This removable backing layer can be directly adhered to one or more surfaces of the adhesive material, or it can be adhered with a layer of glue or other adhesive (such as acrylic adhesive). According to embodiments of the present invention, the integral material layer is made of polysiloxane elastomer, thermoplastic polyurethane, hydrogel, or any other biocompatible material that does not adhere to wet tissue. This integral material layer can be directly adhered to one or more surfaces of the adhesive material.

[0064] According to embodiments of the invention, the adhesive material is in the form of a dry film or strip, which can be applied directly to the surface of interest (e.g., after removing a removable material layer or backing material layer disposed on one or more surfaces of the adhesive material without any additional preparation steps). For example, in a moist physiological environment, biological tissues are typically covered by a thin layer of water. After the adhesive material of the invention is applied, this water or fluid becomes the interfacial fluid between the tissue and the applied adhesive, which typically hinders the formation of a rapid and strong bond between the tissue and the adhesive. To achieve instantaneous and robust adhesion on wet tissue, the adhesive of the invention employs a dry crosslinking mechanism to remove the interfacial fluid and form adhesion on the wet tissue (e.g., as shown in the image). Figure 4A (as shown). For example, under a mild pressure (e.g., 1 kPa) applied for several seconds (preferably less than 5 seconds), (i) one or more hydrophilic polymers or copolymers (e.g., PVA and PAA networks) of the dry adhesive material can absorb interfacial fluids and dry the wet tissue surface.

[0065] Meanwhile, the PAA network (or other suitable hydrophilic polymer / copolymer network) of the adhesive material provides abundant groups (e.g., carboxylic acid groups) that can form transient physical crosslinks (i.e., hydrogen bonds) with the tissue surface (see...). Figure 4A and Figure 5 Furthermore, the cleavable amine (e.g., NHS ester) groups grafted onto the PAA network (or other suitable hydrophilic polymer / copolymer network) form stable covalent crosslinks (i.e., amide bonds) with the abundant primary amine groups on the tissue surface within minutes (e.g., see...). Figure 4A and Figure 5 After adhering to the tissue surface, the swollen bioadhesive becomes capable of at least 7 times the tensile strength and 1000 J / m². -2 Hydrogel thin films with fracture toughness on the order of above.

[0066] According to the present invention, a robust bond between the adhesive material and the desired surface (e.g., a wet tissue surface) depends on both physical and covalent crosslinking, the relative contributions of which differ across different timeframes of the bond. In the short term (<5 minutes), transient physical crosslinking (i.e., hydrogen bonding) dominates the bond between the adhesive material and the surface. The contribution of physical crosslinking to the bond decreases over time because the balancing and subsequent neutralization of carboxylic acid groups in the adhesive material diminishes the adhesive's ability to form physical crosslinks with the tissue surface (e.g., as...). Figure 4B and Figure 5 As described. Therefore, the contribution of covalent crosslinking (i.e., amide bonds) to adhesion gradually increases over a long period of time. Figure 5 ).

[0067] The adhesive of the present invention can be removed from a surface at any time, from immediately after application (e.g., when the adhesive must be repositioned due to initial misplacement) to within minutes of application, to hours of application (e.g., for intraoperative removal of temporary adhesive applied for subsequent final surgical repair), or even days to weeks of application (e.g., in the case of removing implanted devices implanted using adhesive materials). Therefore, the present invention provides an adhesive material with a triggerable removal mechanism, wherein the triggerable removal mechanism is biocompatible and effective over a wide time range.

[0068] According to the present invention, the adhesive material has both physical and covalent crosslinks, which can be cleaved on demand by a biocompatible triggering solution. Figure 4A In particular, this physical crosslinking can be cleaved via pH-dependent decrosslinking, especially through the breaking of hydrogen bonds in the physical crosslinking. Sodium bicarbonate (SBC) is an example of an initiator that can be used to provide cleavage via pH-dependent decrosslinking (e.g., Figure 4B To provide adhesive materials with cleavable covalent crosslinks, cleavable disulfide bonds are introduced between NHS ester groups (amine groups) and one or more hydrophilic polymers or copolymers (e.g., PAA networks) by synthesizing novel functional monomers (see, for example, see [link to other materials]). Figure 6 and Figure 7 Therefore, to cleave these covalent crosslinks, biocompatible reducing agents, such as glutathione (GSH), are used as triggers. Contacting the adhesive, which has been adhered to the surface by cleavable covalent bonds, with such a trigger causes the side thiol groups in the trigger (e.g., GSH) to break the disulfide bonds in the bioadhesive into thiol groups, thereby cleaving the covalent crosslinks between the bioadhesive and the tissue surface. Figure 4C Advantageously, the adhesive material and related cleavage mechanism of the present invention can be realized under physiological conditions, through which both physical bonds and covalent bonds are broken.

[0069] The high processability of the adhesive material of this invention further allows for flexible fabrication into various shapes, such as, but not limited to, flat sheets, perforated sheets, and strip rolls, to meet diverse needs. This adhesive material also possesses several properties advantageous for biological applications. In particular, the adhesive material in its swollen state exhibits a low shear modulus of approximately 20 kPa and stretchability on the order of seven times its original unswollen length, thus comparable to soft tissue properties. Due to its composition, the dry adhesive material can also be manufactured to be highly biocompatible and biodegradable.

[0070] To evaluate the adhesive and triggerable debonding properties of the adhesive material of this invention, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) analysis was used. First, the carboxylic acid content (1698 cm⁻¹) in the adhesive material was determined.-1 ) group, NHS ester (1162 and 1232cm -1 ) group and disulfide (614cm) -1 The combination of groups (see) Figure 8 A). To verify the triggered cleavage of physical and covalent crosslinks of the adhesive, 0.5 M SBC and 50 mM GSH in PBS were used as triggering solutions. Primary amine-coupled fluorescent microbeads were used as a model to evaluate adhesion and delamination between the adhesive and the amine-rich surface of the microbeads. Figure 8 B). Fluorescence microscopy images of the bioadhesive incubated in PBS with amine-coupled fluorescent microbeads for 30 minutes show that the microbeads are stably adhered to the adhesive of the present invention, which is attributed to physical and covalent crosslinking between the adhesive and the microbead surface (see [link]). Figure 7 C and Figure 8 The bioadhesive containing fluorescent microparticles was incubated for 5 minutes in PBS alone, PBS with 0.5 M SBC, and PBS with 0.5 mM SBC and 50 mM GSH, respectively. The bioadhesive incubated in PBS alone showed no significant change in the number of adhered fluorescent microbeads. Figure 8 D and Figure 9 Bioadhesives incubated in PBS with 0.5 M SBC showed a significant reduction in the number of adhered fluorescent microbeads, although most microbeads remained adhered. Figure 8 E and Figure 9 Conversely, the bioadhesive incubated in PBS containing 0.5 mM SBC and 50 mM GSH showed almost complete detachment of the adhered fluorescent microbeads. Figure 8 F and Figure 9 These results indicate that, under physiological conditions, the adhesion of the amine-rich surfaces of the microbeads to the adhesive is stable, and their complete detachment requires the breakdown of both physical crosslinks (via SBC) and covalent crosslinks (via GSH).

[0071] Furthermore, the effect of the triggerable peeling mechanism of this invention on adhesive performance was analyzed. In this analysis, the interfacial toughness between the adhesive material and wet porcine skin tissue was measured according to the standard test for tissue adhesives (180-degree peel test, ASTM F2256). Figure 8 G and Figure 10 ).like Figure 8 As shown in H-8J, the adhesive material of the present invention forms an interfacial toughness of over 400 J / m on wet porcine skin tissue after contact and application of mild pressure (e.g., 1 kPa) for less than 5 seconds. -2 The adhesive demonstrates its strong, instantaneous bonding properties. Furthermore, it has been shown to form a strong, instantaneous bond under various physiological pH conditions, potentially allowing for its use in a wide range of locations within the human body. Figure 11 ).

[0072] To analyze triggerable detachment, the following substances were applied to the adhesive of the present invention adhered to pig skin: PBS alone, PBS with 50 mM GSH, PBS with 0.5 M SBC, and PBS with 0.5 M SBC and 50 mM GSH. Subsequently, the interfacial toughness was measured. Figure 12 and Figure 13 For short-term adhesion (trigger solution applied 1 minute after adhesion formation), samples treated with solutions containing SBC (PBS with 0.5 M SBC, PBS with 0.5 M SBC and 50 mM GSH) showed a significant decrease in measured interfacial toughness, while samples treated with a solution containing GSH alone (PBS with 50 mM GSH) showed negligible difference compared to samples treated with PBS alone. Figure 8 H). This indicates that the ability of SBC and its cleavage physical crosslinking plays a crucial role in the triggerable disintegration of short-term adhesions (disintegration shortly after adhesion, e.g., 1 minute after adhesion). For intermediate adhesions (here, the triggering solution is applied 30 minutes after adhesion formation), all other samples exhibited significantly reduced measured interfacial toughness compared to samples treated with PBS alone. Furthermore, samples treated with a solution containing both SBC and GSH (PBS with 0.5 M SBC and 50 mM GSH) showed significantly lower interfacial toughness than samples treated with a solution containing either SBC or GSH (PBS with 50 mM GSH or PBS with 0.5 M SBC). Figure 7 I). This demonstrates that both SBC and GSH, and their ability to cleave physical and covalent crosslinks, play a crucial role in the triggerable debonding of the adhesive after intermediate bonding. For long-term bonding (solution applied 12 hours after bond formation), samples treated with solutions containing GSH (PBS with 50 mM GSH and PBS with 0.5 M SBC and 50 mM GSH) showed significantly lower interfacial toughness than other samples. Furthermore, samples treated with a solution containing SBC alone (PBS with 0.5 M SBC) showed negligible differences compared to samples treated with PBS alone. Figure 8 This demonstrates that GSH and its ability to cleave covalent crosslinks play a crucial role in the triggerable disintegration of long-term adhesions. These results confirm that a triggering solution of PBS containing 0.5 M SBC and 50 mM GSH can cleave both physical crosslinks (via SBC) and covalent crosslinks (via GSH), and significantly reduce interfacial toughness over a wide timeframe after adhesion formation (Figure 4 and ). Figure 5 ).

[0073] To evaluate the ability of the adhesive material to form rapid, strong, and triggerable detachment adhesion to wet tissue in vivo, the adhesive patch according to the invention was adhered to the muscle layer of the subcutaneous space of rats, and then the detachment of the bioadhesive was triggered as needed. Figure 14 A). It was demonstrated that after 5 seconds of gentle pressure, the adhesive patch adhered to the muscle layer of rats, forming a sufficiently strong adhesion to resist pull-off by forceps. To remove the adhered adhesive patch on demand, a triggering solution was applied to the subcutaneous space of the rats for 5 minutes, which allowed for on-demand removal of the adhesive patch without causing observable damage to the underlying tissue surface. Figure 14 A). Further evaluation of the in vivo biocompatibility and triggerable detachment process of the adhesive in a subcutaneously implanted rat dorsal model ( Figure 14 BE). Histological evaluation by a blinded pathologist indicated that, 2 weeks post-surgery, the triggering solution and triggerable dissection process produced a mild inflammatory response comparable to that produced in the sham control group (surgery without implantation). Figure 14 B, C, and E). Furthermore, histological evaluation of the bioadhesive implanted 2 weeks prior showed a mild to moderate inflammatory response (B, C, and E). Figure 14 (D, E). These results demonstrate the biocompatibility of the adhesive material of the present invention and its ability to trigger delamination.

[0074] Triggerable and non-invasive on-demand removal of bioadhesives can find potential applications in various clinical scenarios across different timeframes. In short timeframes, bioadhesives may be accidentally and incorrectly applied to tissue surfaces, requiring immediate correction for successful surgical treatment. In such clinical scenarios, the triggerable removal provided by the adhesive material of this invention allows for timely correction of incorrectly applied adhesive without damaging underlying tissue. In medium timeframes, emergency treatment of clinically unstable patients often requires initial surgery (e.g., providing a temporary organ seal for initial damage control surgery, where the temporary organ seal may require temporary adhesion for several hours), followed by subsequent final surgical repair. In such clinical scenarios, the triggerable removal of the adhesive of this invention allows for on-demand removal of the adhesive applied during the initial surgery for subsequent final surgical repair. In long timeframes, various medical devices, such as cannulas and drainage tubes in cardiac surgery and drug libraries in localized cancer chemotherapy, require removal days to weeks after implantation. In such clinical scenarios, the adhesive material of this invention, through its provided triggerable removal properties and mechanism, can provide secure fixation of the device and non-invasive retrieval.

[0075] To investigate the potential applications of the removable adhesive material of this invention, an ex vivo principle demonstration was applied to a pig organ. To demonstrate the potential advantages of the instantaneous strong adhesion and triggerable removability of the adhesive material in this case, successful repositioning of the adhesive was demonstrated on a pig lung (3 cm incision) that was initially only partially sealed. Figure 15 A). For example Figure 15 As shown in Figure B, improperly adhered adhesive material was easily removed within 5 minutes of applying the triggering solution. Importantly, subsequent application of new adhesive rapidly formed an airtight seal in the pig lung without compromising adhesion properties. Figure 16 ).

[0076] In another example, the adhesive device according to the invention demonstrated instantaneous strong bonding and on-demand removal on wet dynamic tissue. Since many devices are not readily permeable to the triggering solution of the invention, a patterned bioadhesive was designed to facilitate the transport and diffusion of the triggering solution to the bonding interface. Figure 15 C). For example Figure 15 As shown in D, the patterned bio-adhesive according to the invention is provided on an impermeable thermoplastic polyurethane (TPU) membrane, which allows for easy transport and diffusion of the trigger solution (dyed red by an edible dye) through the adhered device. The simulated device, consisting of gold-plated polyimide and the patterned bio-adhesive according to the invention, has further demonstrated rapid and strong adhesion to a beating isolated pig heart (simulated by introducing pressurized air input), and is removable on demand. Figure 15 E). Due to the instantaneous and robust adhesion of the adhesive material of this invention, the bioadhesive device is able to form a strong and stable adhesion on a beating pig heart within 5 seconds of application. Furthermore, the application of the trigger solution allows for non-invasive removal of the adhered device within 5 minutes. Figure 15 F). Therefore, the ability of the adhesive material of the present invention to form instantaneous and strong adhesion on wet dynamic tissue and its on-demand detachment may be particularly advantageous for the integration of implantable devices and potential non-invasive removal.

[0077] In addition to providing this beneficial on-demand triggerable removal mechanism, the adhesive material of this invention further provides compatibility with existing tissue adhesives (including commercially available cyanoacrylate adhesives, such as Histoacryl Flex). TM Dermabond TM ), albumin-based adhesives (e.g., Bioglue) TM ), polyethylene glycol-based adhesives (e.g., CoSeal) TM DuraSeal TM ), fibrin glue (e.g., Tisseel) TMCompared to nanoparticle solutions and UV-curable surgical adhesives, this invention offers faster and superior bonding performance. The adhesive material of this invention is suitable for a wide range of wet tissues, including skin, tendons, stomach, muscles, heart, and liver. Thus, the adhesive can be particularly effective as a promising alternative to sutures or staples in surgical repair or wound closure. The rapid and strong bonding properties of the dry adhesive material are also ideal for attaching various functional devices to dynamic and deformable tissues, allowing for instantaneous and robust bonding between wet tissues and various engineered solids, including hydrogels, silicone, titanium, polydimethylsiloxane (PDMS), polyimide, and polycarbonate, which is not possible with existing tissue adhesives. In other words, the dry adhesive material of this invention can be used to attach one or more engineered solids to one or more wet tissue surfaces.

[0078] Therefore, based on a dry crosslinking mechanism that provides rapid and strong adhesion to various wet tissues and devices, this invention provides an improved tissue adhesive in the form of an adhesive material, preferably in the form of a dry film or strip, and for certain applications, in the form of a dry double-sided film or strip. The dry, storable, and readily available nature of the adhesive material provides extended storage, dispensing, and use convenience (e.g., over two weeks) without loss of performance. Thus, the adhesive material of this invention eliminates the difficulties common in existing tissue adhesives, such as storing perishable liquids or wet gels and mixing reagents before each use. Furthermore, the pre-designed adhesive material is a simple composition with high manufacturing flexibility. This can thus offer significant economic advantages, potentially facilitating the rapid and widespread dissemination and transformation of materials. These novel features of the adhesive material, in its excellent adhesion properties to various surfaces, including wet tissues, and its ability to be removed on demand without trauma to fragile tissues, address a number of long-standing challenges in existing tissue adhesives and offer new opportunities for the future development of tissue engineering, drug delivery, and bio-integrated devices. The dry crosslinking mechanism for wet adhesion can further inspire the design of future adhesives in wet and underwater environments.

[0079] Materials and methods of exemplary embodiments Synthesis of NHS ester functionalized monomers with disulfide bonds To prepare NHS ester-functionalized monomers with disulfide bonds, 1.8 g (10.0 mmol) of 2,2'-dithiodiacetic acid and acetic anhydride (8.0 mL) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. The mixture was stirred at room temperature for 3 hours to obtain a homogeneous solution. Figure 6A). The solvent was then removed under vacuum to give a pale yellow oil, 1,4,5-oxadithiaheptane-2,7-dione. The oil was directly transferred to a mixture of 2-hydroxyethyl methacrylate (1.9 g, 15.0 mmol), 4-dimethylaminopyridine (DMAP; 12.0 mg, 1.0 mmol), and 15 mL of anhydrous dichloromethane (DCM). The solution was stirred overnight at room temperature, and the reaction was terminated by adding 30 mL of saturated NaHCO3 solution. Figure 6 B). The mixture was then acidified to pH 2.0 with 1M HCl and extracted with DCM. The organic phase was dried over Na₂SO₄ and concentrated under reduced pressure. The crude product was purified by rapid column chromatography on silica gel using a mixture of MeOH and DCM (v / v = 1 / 20) as eluent to give 6-(2-(methacryloyloxy)ethoxy)hept-6-enoic acid. 6-(2-(methacryloyloxy)ethoxy)hept-6-enoic acid (2.94 g 10.0 mmol) was then dissolved in 30 mL of anhydrous DCM and... N 1-Hydroxysuccinimide (NHS; 1.15 g, 10 mmol) was stirred in an ice bath for 30 minutes. Then, 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide hydrochloride (EDC; 1.55 g, 10 mmol) in 20 ml of DCM was added dropwise to the above mixture. The solution was stirred overnight at room temperature under a nitrogen atmosphere. Figure 6 C). The crude product was purified by rapid column chromatography on silica gel using a mixture of petroleum ether and ethyl acetate (v / v = 1 / 1) as the eluent to obtain a colorless liquid product. 1 H NMR (400 MHz, CDCl3, δ): 6.17 (p, 1H,-CH2), 5.59 (q, 1H, -CH2), 4.44-4.33 (m, 4H, -OCH2CH2O-), 3.83-3.68 (d, 4H, -CH2SSCH2-), 2.85 (s, -CH2-CH2-) 1.94 (s, 3H, -CH3)( Figure 7 ).

[0080] Preparation of bioadhesives To prepare the bio-adhesive, polyvinyl alcohol (PVA; Mw=146000-186000, 7 w / w%), acrylic acid (AAc; 35 w / w%), α-ketoglutaric acid (0.2 w / w%), and poly(ethylene glycol methacrylate) (PEGDMA; Mn=550, 0.05 w / w%) were dissolved in deionized water. Then, 100 mg of a functional monomer (an NHS ester-functionalized monomer with disulfide bonds) was dissolved in 1 ml of acetone and added to 10 ml of the above stock solution to obtain a precursor solution. The precursor solution was then poured onto a glass mold with spacers (210 μm thick unless otherwise specified) and cured in a UV chamber (284 nm, 10 W power) for 30 minutes. As a non-adhesive layer, a 10 w / w% thermoplastic polyurethane solution was spin-coated onto the cured bio-adhesive at 400 rpm for 30 seconds and allowed to dry completely. The prepared bioadhesive was sealed in a plastic bag containing a desiccant (silicone packet) and stored at -20°C before use. To pattern the bioadhesive, a large sheet was cut into various patterns using a laser cutter (Epilog). Weighing paper (VWR) was used as a removable backing for the bioadhesive.

[0081] Preparation of trigger solution To prepare the trigger solution, 0.5 M sodium bicarbonate (SBC) and L-reduced glutathione (GSH) were dissolved in PBS. The trigger solution was filtered using a 0.2 µm sterile syringe filter before use. To verify the triggerable detachment of the bioadhesive, the bioadhesive was placed on fluorescent microbeads (FluoSpheres) with primary amine conjugation. TM The samples were incubated in PBS (Thermo Fisher Scientific) at room temperature for 30 minutes. Then, the samples were further incubated for 5 minutes in various trigger solutions, followed by thorough washing with clean PBS to remove unadhered microbeads. The presence of adhered microbeads was characterized using a fluorescence microscope (LV10, Nikon), and the number of adhered microbeads was counted using Image-J.

[0082] Mechanical testing For tissue samples stored for more than 10 minutes prior to mechanical testing, the samples were covered with a large amount of 0.01 w / v% sodium azide solution (in PBS) and sealed in plastic bags to prevent tissue degradation and dehydration. Unless otherwise specified, all tissues and engineered solids were adhered to the adhesive material after rinsing the surface with PBS and then pressing for 5 seconds (using a mechanical testing machine or applying 1 kPa pressure of equivalent weight). To measure interfacial toughness, adhered samples with a width of 2.5 cm were prepared and tested using a mechanical testing machine (2.5 kN load cell, Zwick / Roell Z2.5) via a standard 180-degree peel test (ASTM F2256). All tests were performed at 50 mm min. -1 The peeling process was carried out at a constant peeling rate. As the peeling process reached a steady state, the measured force reached a stable level. The interfacial toughness was determined by dividing twice the stable level force by the width of the tissue sample. Figure 10 A hydrophilic nylon filter (1µm pore size, TISCH Scientific) was applied as a rigid backing for the adhesive material. A poly(methyl methacrylate) film (50µm thick, Goodfellow) was applied as a rigid backing for the tissue using cyanoacrylate glue ((Krazy Glue)). Unless otherwise specified, interfacial toughness was measured 5 minutes after application of the trigger solution.

[0083] FTIR characterization The chemical composition of the adhesive material was characterized using a transmission Fourier transform infrared spectrometer (FTIR6700, Thermo Fisher) with a germanium attenuated total reflectance (ATR) crystal (55 degrees).

[0084] In vivo biocompatibility assessment All animal surgeries were reviewed and approved by the MIT Animal Care Committee. All in vivo studies used female Sprague Dawley rats (225–250 g, Charles River Laboratories). Adhesives were prepared using aseptic techniques prior to implantation and further sterilized under UV light for 3 hours. Rats were anesthetized in an anesthesia room using isoflurane (1–2% isoflurane in oxygen) to create the subcutaneous space in the back. Anesthesia was maintained using a nasal cone. Hair was removed from the back, and the animals were placed on a heating pad during the procedure. Each implant was inserted into the subcutaneous space in the center of the animal's back through a 1–2 cm skin incision. Blunt dissection was performed from the incision to the animal's scapula to create space for implant placement. For the sham surgery group, no implant was placed in the subcutaneous pouch (n=4). For the triggerable removal group, a bio-adhesive (10 × 20 mm) was placed in the subcutaneous pouch created above the incision and removed 5 minutes after the application of 1 mL of trigger solution (n=4). For the bioadhesive implantation group, the bioadhesive (10 mm wide and 20 mm long) was placed in a subcutaneous pouch created above the incision, without removal (n=4). The incision was closed using interrupted sutures (4-0 Vicryl, Ethicon), and 3-6 ml of saline was injected subcutaneously. A maximum of three implants were placed per animal, ensuring no overlap between the created subcutaneous pouches. Two weeks after implantation, the animals were euthanized by CO2 inhalation. The subcutaneous area of ​​interest was excised and fixed in 10% formalin for 24 hours for histological analysis.

[0085] Histological treatment Fixed tissue samples were placed in 70% ethanol and submitted to the Hope Babette Tang (1983) histology facility at the Koch Institute for Integrative Cancer Research, MIT, for histological processing and hematoxylin and eosin (H&E) staining. Histological evaluation was performed by blinded pathologists on a scale of 0–5 (0, normal or absent; 1, very slight or minimal; 2, mild; 3, moderate; 4, severe or significant; 5, very severe) to assess the degree of inflammation in the tissue surrounding the subcutaneous implant. The degree of acute inflammation was based on the number of neutrophils. The degree of chronic inflammation was based on the presence of lymphocytes, macrophages, and plasma cells. The degree of inflammation was assessed based on the overall presence of indicators (absent, minimal, mild, moderate, or significant) in each histological sample. Representative images of each group are shown in the corresponding figures.

[0086] In vitro experiments All in vitro experiments were reviewed and approved by the MIT Animal Care Committee. To correct misplaced bioadhesive, a laceration was created on the pig lung lobe using a 3cm razor blade. Air was then applied (25mmHg pressure) through a tube attached to the upper part of the trachea to make the air leak visible. A bioadhesive (2.5cm wide and 5cm long) was applied to the damaged lung lobe and pressed for 5 seconds to partially cover the laceration to indicate misplacement and incomplete sealing. The misplaced bioadhesive was covered with medical gauze, and a triggering solution was applied to the gauze. Five minutes after the application of the triggering solution, the misplaced bioadhesive was removed with forceps. To seal the exposed laceration, new bioadhesive was applied to completely cover the laceration, and an airtight seal was confirmed by circulating and deflating the pig lung.

[0087] For the adhesion and on-demand removal of the bioadhesive device, a simulated device with gold-plated polyimide and patterned bioadhesive (2 cm wide, 4 cm long, with the bioadhesive pattern having a width of 1 mm and a gap of 1.5 mm) was adhered to a beating isolated pig heart. The aorta of the heart was connected to a tube, and a microdispenser (Ultimus) was used. TM (V, Nordson EFD) A programmed pressurized air input was introduced into the pig heart to simulate a heartbeat. The device adhered to the beating heart was kept at room temperature for 3 hours, during which the beating was continuous, and then the adhesion was checked by pulling with tweezers. The bioadhesive device was covered with medical gauze, and a triggering solution was applied to the gauze. Five minutes after the application of the triggering solution, the bioadhesive device was removed with tweezers, and the tissue damage on the surface of the pig heart was examined. To prevent dehydration and degradation, a damp towel soaked in 0.01 w / v% sodium azide solution (in PBS) was placed over the heart for experiments lasting more than 1 hour under ambient conditions.

[0088] Statistical analysis MATLAB software was used to evaluate the statistical significance of all comparative studies in this work. It was assumed that the data distributions for all parameter tests were normal, but no formal tests were performed. In the statistical analysis used for comparisons between multiple samples, one-way ANOVA was performed, followed by Tukey multiple comparison trials with a threshold of [value missing]. p≤0.05, p≤0.01 and p≤0.001. In the statistical analysis between the two data groups, a two-sample Student's t-test was used, with a significance threshold set to [value missing]. p≤0.05, p≤0.01 and p≤0.001.

Claims

1. An adhesive material for bonding one or more wet surfaces and for triggerable detachment from said one or more wet surfaces, said adhesive material comprising: In a dry state, an interpenetrating network of (i) polyvinyl alcohol (PVA) and poly(acrylic acid) (PAA), wherein the poly(acrylic acid) is grafted with (ii) N-hydroxysuccinimide (NHS) ester via (iii) cleavable disulfide bonds, and (iv) one or more crosslinking agents. The adhesive material is in the form of a film or strip having a top surface and a bottom surface. The adhesive material has liquid contents such that placement of one or more of its top and / or bottom surfaces in contact with the one or more wet surfaces causes the adhesive material to absorb liquid from the one or more wet surfaces, swell to form a temporary crosslink between the dry adhesive material and the wet surfaces, and form covalent bonds between the N-hydroxysuccinimide ester and the one or more wet surfaces. The adhesive material is detached from the one or more wet surfaces on demand using a triggering agent comprising a solution containing a combination of sodium bicarbonate and glutathione.

2. The adhesive material according to claim 1, wherein, The one or more crosslinking agents mentioned in (iv) are selected from gelatin methacrylate, hyaluronic acid methacrylate, oxidized alginate methacrylate, polycaprolactone diacrylate, etc. N,N' -Bis(acryloyl)cystamine, N,N' - Methylene bis(acrylamide), polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and combinations thereof.

3. The adhesive material according to claim 1, wherein, Grafting has N - The negatively charged carboxylic acid groups in the poly(acrylic acid) of hydroxysuccinimide ester promote liquid absorption and swelling of the dry adhesive material, and further form intermolecular bonds with one or more wet tissue surfaces within 60 seconds after the dry adhesive material comes into contact with the one or more wet tissue surfaces.

4. The adhesive material according to claim 1, wherein, The N-hydroxysuccinimide ester grafted onto poly(acrylic acid) forms a cleavable covalent bond with a primary amine group present on the one or more wet surfaces.

5. The adhesive material according to claim 1, wherein, After covalent crosslinking is formed between the N-hydroxysuccinimide ester and the one or more wet surfaces, the swollen adhesive material transforms into a hydrogel.

6. The adhesive material according to claim 5, wherein, The hydrogel has a density of at least approximately 1000 J / m. -2 Fracture toughness.

7. The adhesive material according to claim 1 is in the form of a flat sheet, a perforated sheet, a double-sided tape or film, or a perforated double-sided tape or film.

8. The adhesive material according to claim 7, wherein, The adhesive material includes a top surface and a bottom surface, and wherein the adhesive material further includes one or more backing material layers disposed on at least one of the top surface and the bottom surface.

9. The adhesive material of claim 1, further comprising one or more engineered solids and / or devices adhered to one or more surfaces of the adhesive material.

10. The adhesive material according to claim 1, wherein, The adhesive material is biodegradable.

11. Use of an adhesive material in the preparation of a medicament for bonding wet tissue and for removal from said wet tissue as needed, comprising: The adhesive material is provided, comprising: in a dry state (i) an interpenetrating network of polyvinyl alcohol (PVA) and poly(acrylic acid) (PAA), wherein the poly(acrylic acid) is grafted with (ii) N-hydroxysuccinimide (NHS) ester via (iii) cleavable disulfide bonds, and (iv) one or more crosslinking agents. The adhesive material is removed from the wet tissue on demand using a triggering agent, which includes a solution containing a combination of sodium bicarbonate and glutathione.

12. The use according to claim 11, wherein, The one or more crosslinking agents mentioned in (iv) are selected from gelatin methacrylate, hyaluronic acid methacrylate, oxidized alginate methacrylate, polycaprolactone diacrylate, etc. N,N' -Bis(acryloyl)cystamine, N,N' - Methylene bis(acrylamide), polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and combinations thereof.

13. The use according to claim 11, wherein, Under a pressure of no more than about 1 kPa applied for no more than 5 seconds, the PVA and PAA networks absorb liquid, causing one or more wet surfaces of the wet tissue to dry, wherein the PAA network provides carboxylic acid groups that form transient physical crosslinks with one or more surfaces of the wet tissue via hydrogen bonds.

14. The use according to claim 11, wherein, The cleavable NHS ester groups grafted onto the PAA network form stable covalent crosslinks with primary amine groups on one or more surfaces of the wet tissue.

Citation Information

Patent Citations

  • Controllably removed strong adhesion type hydrogel and preparation method thereof

    CN111057252A

  • Tissue-adhesive materials

    CN1993149A